2006
DOI: 10.1046/j.1360-0443.1995.90810534.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and suicide-the Portuguese experience

Abstract: An analysis of regional (18 regions) and temporal (1931-89) covariation of suicide rates and indicators of alcohol use and abuse in Portugal is reported. In the time series analysis, a positive relationship was found. An increase in per capita alcohol consumption of one litre is accompanied by a simultaneous increase in the male suicide rate of 1.9 per cent. This is comparable to what has been reported for France and Denmark, but considerably less than that found in Norway, Sweden and Hungary. In the regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Also, in a previous study performed in 1980–1982 in Portugal, the inverse association between suicide rates and alcohol cirrhosis deaths had a distinctive regional distribution: whereas in the north, alcohol uptake and cirrhosis death was greater than in the south, suicide rates were much greater in the south [22], suggesting that alcohol addiction is on many occasions either a depression equivalent or a self-medication strategy [24]. Overall, cultural differences are also important in explaining variation in the associations across countries.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Also, in a previous study performed in 1980–1982 in Portugal, the inverse association between suicide rates and alcohol cirrhosis deaths had a distinctive regional distribution: whereas in the north, alcohol uptake and cirrhosis death was greater than in the south, suicide rates were much greater in the south [22], suggesting that alcohol addiction is on many occasions either a depression equivalent or a self-medication strategy [24]. Overall, cultural differences are also important in explaining variation in the associations across countries.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, differing approaches in these studies to controlling for potential confounds are challenging for integration and interpretation. In some settings and contexts, economic development correlates with lower suicide rates [20], [21], while alcohol consumption [22][24], divorce both in men and women [25], [26] and unemployment [27], [28] can correlate with higher suicide rates.…”
Section: Introductionmentioning
confidence: 99%
“…Using similar time series methods, estimates of national level per capita alcohol consumption, and employing few covariates beyond unemployment and divorce rates as measures of Durkheim's social integration, a positive association of alcohol consumption with suicide has been shown in Sweden (Rossow, 1993); Norway (Norstrom, 1988); France (Norstrom, 1995); Hungary (Skog and Elekes, 1993); in Portuguese men (Skog et al, 1995); and in younger, under age 45, Finnish men (Makela, 1996). No relationship was found, however, between aggregate alcohol consumption and suicide among Portuguese women (Skog et al, 1995) nor among Swiss women, and a weak negative relationship was found for Swiss men (Gmel et al, 1998). In the United States, Wasserman (1989) found that suicide rates decreased during the U.S. prohibition era; Gruenewald and colleagues (1995) found that suicide rates were related to per capita consumption of spirits, but not beer or wine; and Caces and Harford (1998) found that alcohol consumption increased the suicide risk for men and women younger than age 60 when unemployment was included in their models.…”
mentioning
confidence: 99%
“…Drinking patterns and the strength of their association with suicidal behaviour in adolescents appear to differ between European countries [26,58] and seem to be stronger in the northern, eastern and central European countries compared to southern Europe [4,57,[61][62][63][64]. Ramstedt proposed that the less intoxication-orientated drinking pattern of southern European countries appears to be more resistant to an elevated suicide-risk in younger age groups [61].…”
Section: Alcohol and Drug Abusementioning
confidence: 99%